Lubiprostone Improves Distal Segment-Specific Colonic Contractions through TRPC4 Activation Stimulated by EP3 Prostanoid Receptor - Byeongseok Jeong; Jun Hyung Lee; Jin-A Lee; Seong Jung Kim; Junhyung Lee; Insuk So; Jae Yeoul Jun; Chansik Hong (MDPI AG, 2024)
Background: Prokinetic agents are effective in increasing gastrointestinal (GI) contractility and alleviating constipation, often caused by slow intestinal motility. Lubiprostone (LUB), known for activating CLC-2 chloride channels, increases the chloride ion concentration in the GI tract, supporting water retention and stool movement. Despite its therapeutic efficacy, the exact mechanisms underlying its pharmacological action are poorly understood. Here, we investigated whether LUB activates the canonical transient receptor potential cation channel type 4 (TRPC4) through stimulation with E-type prostaglandin receptor (EP) type 3. Methods: Using isotonic tension recordings on mouse colon strips, we examined LUB-induced contractility in both proximal and distal colon segments. Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to determine mRNA levels of EP1-4 receptor subtypes in distal colonic muscular strips and isolated myocytes. The effects of a TRPC4 blocker and EP3 antagonist on LUB-stimulated contractions were also evaluated. Results: LUB showed significant contraction in the distal segment compared to the proximal segment. EP3 receptor mRNA levels were highly expressed in the distal colon tissue, which correlated with the observed enhanced contraction. Furthermore, LUB-induced spontaneous contractions in distal colon muscles were reduced by a TRPC4 blocker or EP3 antagonist, indicating that LUB-stimulated EP3 receptor activation may lead to TRPC4 activation and increased intracellular calcium in colonic smooth muscle. Conclusions: These findings suggest that LUB improves mass movement through indirect activation of the TRPC4 channel in the distal colon. The segment-specific action of prokinetic agents like LUB provides compelling evidence for a personalized approach to symptom management, supporting the defecation reflex.